1991
DOI: 10.1177/070674379103600614
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Consultation with Children in Underserviced Areas: Lessons from Experiences in Northern Ontario

Abstract: There are only 350 child psychiatrists in Canada. It is therefore unrealistic to expect them to be able to provide sufficient direct treatment, even in small densely populated communities with abundant resources. Such expectations are even more unrealistic in underserviced, sparsely populated areas. A review of the literature on psychiatric consultation in underserviced areas is presented along with a description of the consultation process, taking advantage of the "multiplier effect." Some of the realities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…After studying community health aides in Alaska, Caldera et al (1991) concluded that they were able to provide complete basic primary care to more than 85% of patients presenting at community clinics. DuBois et al (1991) have also advocated the use of community-based intervenors, linked to psychological resources in larger centers, to sustain mental health services for children in underserved rural areas. Hassinger (1982) andD'Augelli (1982) have viewed the paraprofessional, primarily, as extending the professional's ability to function.…”
Section: Literaturementioning
confidence: 99%
“…After studying community health aides in Alaska, Caldera et al (1991) concluded that they were able to provide complete basic primary care to more than 85% of patients presenting at community clinics. DuBois et al (1991) have also advocated the use of community-based intervenors, linked to psychological resources in larger centers, to sustain mental health services for children in underserved rural areas. Hassinger (1982) andD'Augelli (1982) have viewed the paraprofessional, primarily, as extending the professional's ability to function.…”
Section: Literaturementioning
confidence: 99%
“…For instance, at various times and in various locations there have been lamentations about shortages of child psychiatrists (e.g. Dubois, Nugent & Broder, 1991;Rae-Grant, 1986;for Canada;Beresin & Borus, 1989; for the U.S.A.; Health Advisory Service, 1986;Kurtz, Thornes & Wolkind, 1995; for the U.K.), There have been similar comments about shortages of clinical, educational and child psychologists, paediatricians, psychotherapists, social workers, drugs and so on. Indeed, virtually every resource employed in the treatment of the psychiatric disorders of ECONOMIC EVALUATIONS AND INTERVENTIONS childhood and adolescence appears to be scarce relative both to the needs that have been uncovered (see following) and to levels of expressed demand backed by the ability to pay for it.…”
Section: Latetit Detnands For Economic Evaluationmentioning
confidence: 99%
“…), sendo mais interessante, durante o processo de interconsulta, elaborar relatos concisos e direcionados, incluindo dados a respeito do diagnóstico, objetivos do tratamento e considerações de ordem prática, quanto ao manejo e prognóstico do caso (CHAN, 1996 -QUADRO 4.1). Dubois et al (1991) sugerem algumas diretrizes a serem seguidas com o intuito de conduzir, de forma adequada e satisfatória, o processo de interconsulta: et al, 1988). Dessa maneira, o desafio é sempre o desenvolvimento de maneiras mais efetivas de utilizar as habilidades do psiquiatra da infância, uma vez que seu número dificilmente atingirá a quantidade necessária para que ele mesmo efetue o atendimento direto da criança, na maioria dos casos (RAE-GRANT, 1986;FROESE et al, 1997).…”
Section: Discussionunclassified
“…Assim, considerando que o interconsultor atua em numerosos domínios, sendo seu cliente não somente a criança, mas também os pais e os demais membros da equipe, seria necessário um "efeito multiplicador", descrito por Dubois et al (1991), no qual o psiquiatra da infância deveria, a partir da consultoria e supervisão a outros profissionais envolvidos diretamente nos cuidados com a criança, introduzir conceitos de prevenção, diagnóstico e tratamento a outros profissionais, fornecendo a liderança em serviços que se encontram em desenvolvimento. Stein (1992) , uma vítima" (KREISLER, 1999).…”
Section: Discussionunclassified